PENGEMBANGAN PODCAST EDUKATIF PENDEWASAAN USIA PERKAWINAN BAGI ANGGOTA PIK-R - Sherly Septiani Mulya; Andromeda Valentino Sinaga; Dedy Aswan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Educational activities on Delaying the Age of Marriage (PUP) are one of the efforts to equip adolescents with knowledge and understanding regarding family life planning. However, the implementation of education in PIK-R activities is still dominated by lecture-based methods, so the use of learning media that supports student engagement has not been optimal. This study aims to develop an educational podcast as a learning medium for the Marriage Age Maturity program for PIK-R members. This study employs the Research and Development (R&D) method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of subject matter experts, media experts, learning experts, PIK-R supervising teachers, and PIK-R members from Bantaeng State High School 1 who participated in small-group and large-group pilot tests. Data were collected through observation, interviews, documentation, and questionnaires, then analyzed using quantitative and qualitative descriptive techniques. The results of the needs analysis indicated that PIK-R members required learning media that was easily accessible, flexible, and suited to the learning characteristics of adolescents. Based on these needs, an educational podcast in the form of a dialogue was developed and published on the Spotify platform. Validation results showed a 93% approval rate from subject matter experts, 96.67% from media experts, and 96.87% from learning experts, all categorized as “highly valid.” User responses also showed excellent results: 91.67% in the small-group test, 95% in the large-group test, and 95% among PIK-R supervising teachers. The research findings indicate that the educational podcast is suitable for use as a learning medium for the “Marriage Age Maturity” program and has the potential to serve as an alternative medium supporting the implementation of PIK-R educational activities in schools.